Lohmannella africana Bartsch 1992 - Abé, Hiroshi (Zenodo, 2021)
Lohmannella africana Bartsch, 1992 Diagnosis. Corneae absent. Glp-1 same level as Ds-1. Ds-2 and Ds-3 on membranous cuticle. Two dorsal setae on PE. Female with 16 Pgs and 10 Sgs. Tr I–II with 1-1 setae; Bf I–IV with 2-2-?-3 setae; Tf I–IV with 5-6-4-3 setae; Gn I–IV with 8-6-4-4 setae, 4-1-?-1 Bp setae; Tb I–IV with 10-9-8-8 setae, 6-4-2-2 Bp setae; Ta I–IV with 3-3-4-3 dorsal setae, 1-1-2-1 Bp setae. Lc I with unidentate accessory process. Idiosoma length 378, width 260 in female. Gnathosoma length 266 in female. Ratio of gnathosoma to idiosoma 0.704. Ratio of P-2 to P-1 4.29. Remarks. This species was described by Bartsch (1992) on the basis of a single female specimen. The species is similar to L. grandipora Newell, 1984. L. africana is distiguishable from the latter by the presence of dorsal panels on PD. A single female is known. Habitat. Littoral zone: Coarse shell fragments on beach. Distribution. Indian Ocean: Gonubie (East London) [South Africa]. Reference. Bartsch (1992). Depository. SMF. : Published as part of Abé, Hiroshi, 2021, Taxonomic review of the subfamily Lohmannellinae (Acari: Trombidiformes Halacaridae) with morphological comparisons among genera, pp. 201-255 in Zootaxa 4980 (2) on page 209, DOI: 10.11646/zootaxa.4980.2.1, http://zenodo.org/record/4888860 : {"references": ["Bartsch, I. (1992) Lohmannella dictyota n. sp. und L. africana n. sp. von der Sudhalbkugel (Arachnida: Acari: Halacaridae). Senckenbergiana biologica, 72, 457 - 464.", "Newell, I. M. (1984) Antarctic Halacaroidea. Antarctic Research Series, 40, 1 - 284."]}